Adoption of technology in recruitment of library professionals and faculty members: Case study of social media in India. Issue 4 (14th November 2016) - Yuvaraj, Mayank
Abstract : Purpose: This paper aims to attempt to study the adoption of social media technologies in the process of recruitment and selection process of library professionals and faculty members in India. Design/methodology/approach: Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model was used for the study. Two additional constructs, namely, impact of the position of recruiters and level of education were added for the study. Data were collected from 230 recruiters for the study. Findings: Results of the study highlighted that the hypotheses of UTAUT model were supported. The constructs were performance expectancy, effort expectancy, social influence as well as facilitating conditions that triggered the behavioral intention of recruiters to adopt social media. Originality/value: Till date, no any study has been carried out on the application of social media in the process of recruitment of faculty members and library professionals.